Correlation between productivity traits and protein percentage in pea seeds in the conditions of Donbass - V. N. Gelyukh; A. R. Ashiev; A. V. Baranovsky; A. S. Sadovoy (Зерновое хозяйство России)
The solution to the most urgent problem of stable and smooth production of vegetable protein in the agro industrial complex of Donbass is practically impossible without introducing new pea varieties into production, the main legume of the region. The main tasks set by the breeders are to improve productivity stability over the years and the overall productivity potential by developing and introducing new, more environmentally ﬂexible and adapted to speciﬁc growing conditions genotypes into production. In this regard, there has been given a special role to improving a number of quantitative traits that directly or indirectly aﬀect the overall productivity of plants. The purpose of the current research was to identify the closeness and direction of the correlation of traits that determine productivity and protein percentage in pea seeds, their stability and variability depending on weather changes during a vegetation period. The weather conditions of 2022–2024 were very contrasting, which allowed evaluating the signiﬁcance of each productivity element in more detail. There has been found that close correlations between seed weight per plant and a number of seeds per plant (r = 0.79***…0.83***), as well as a number of beans per plant (r = 0.69**…0.80***), between a number of beans and seeds per plant (r = 0.79***…0.85***) were studied in relatively favorable years (2022 and 2023). Identiﬁcation of valuable breeding material by indirect traits in extreme years (2024), when the HTC < 0.2, was signiﬁcantly complicated. All the obtained correlation coeﬃcients under these conditions were low and unreliable. The results of the correlation of protein percentage in pea seeds with yield structure elements did not reveal a clear correlation between these traits. The correlation between protein percentage in pea seeds and yield structure elements has not been identiﬁed due to low and unreliable correlation coeﬃcients, which allows directing pea breeding towards increasing protein percentage in seeds without taking into account the eﬀect of seed productivity.